Belt and Road Initiative: Regional and Global Dimensions - Prof. Dr. Muhammad Iqbal Chawla (Journal of Political Studies, 2018)
This paper is an attempt to explore the regional significance and global dimensions of the Chinese President Xi Jin Ping’s vision and initiative regarding Belt and Road which can transform adjacent countries like Afghanistan, Central Asian Republican States (CARS), India, Iran, Nepal and Pakistan into a real economic hub in coming time. Belt and road initiative is a mega project which includes; massive road connectivity, geographical linkages, rail and road transportation system, people to people contacts, development of understanding through cultural, academic, business and professional exchanges for the progress and prosperity of this vast region. In fact, the initiative of China Pakistan Economic Corridor is one of the mega projects which focuses; the creation of new regional connectivity through Gwadar Sea Port, giving direct access to Chinese goods from Kashgar (China) towards Gwadar (Pakistan). Hence, this development of faster infrastructure of rail, roads, towards maritime transportation and communication is an important project which can connect the countries of the area like Afghanistan, India, Nepal, Central Asia as well as Iran. Thus, the Gwadar Port will connect China, Russia, Middle East, Central Asia and South East Asia. The OBOR and CPEC are a burning issue and much debated topic in today’s Pakistan and world at large. In Pakistan mostly people believe that the CPEC will be a major source of economic development, peace and prosperity. On the one hand, US and India nexus, is trying to develop negative image about the project of CPEC by creating the impression of another colonial domination on the Pakistan territory in the form of Chinese presence. India is making all efforts, to sabotage and to damage the credibility of the CPEC project. This paper by delving and investigating the OBOR and CPEC connections will try to encapsulate the regional importance, dimensions of the project of Belt and Road initiative.